Art matters : because your imagination can change the world - Gaiman, Neil; Gaiman, Neil; Gaiman, Neil; Gaiman, Neil; Gaiman, Neil ([New York] : William Morrow, an imprint of HarperCollins Publishers, 2018)
Collects four of the award-winning author's short works on the importance of freedom of expression, imagination, creation, libraries, and reading to change people and the world for the better.
Credo -- Make good art -- Making a chair -- On libraries.
Keywords: Gaiman, Neil -- Philosophy; Gaiman, Neil -- Philosophy; Creation (Literary, artistic, etc.); Creative ability; Reading; Imagination; Authorship; Art -- Philosophy; Freedom of expression; Creation (Literary, artistic, etc.); Creative ability; Reading; Imagination; Authorship; Art -- Philosophy; Freedom of speech